CREDIT RISK MANAGEMENT AND CREDIT RISK ANALYSIS (CASE STUDY OF BUMN’S BANK 2018-2019) - Nenden Ayu; Estu Widarwati (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2020)
This study aims to describe the credit risk management and credit risk of goverment banking of Indonesia listed IDX in 2018-2019. The study was conducted descriptively, and secondary data was collected based on a review of documents sourced from annual reports and financial report of state-owned banking. Analyzed data show credit risk management of BUMN bank seem good based on capital adequancy ratio (CAR) value above Indonesia central bank rule that average of 74%. But there is a waening signal of credit risk in BUMN banking because the data find a high number of average credit risk. Furthermore, the study find a positive trend between CRM and Credit Risk in state-owned banking. A high level of CAR needed by bank for minimilizing its credit risk